2013
DOI: 10.1093/chemse/bjt046
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Sugar Modifies Behavioral but not Taste-Evoked Medullary Responses to Sweeteners in Mice

Abstract: Dietary exposure to sugars increases the preference for and intake of sugar solutions in mice. We used brief-access lick tests and multiunit electrophysiological recordings from the nucleus of the solitary tract (NST) to investigate the role of taste in diet-induced changes in sucrose responsiveness. We exposed C57BL/6J (B6) and 129X1/SvJ (129) mice to either a sucrose diet (chow, water, and a 500mM sucrose solution) or a control diet (chow and water) for 3 days. In B6 mice, exposure to the sucrose diet decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In brief-access lickometry, taste stimuli are presented for a short (seconds) duration. The output lick rate is not directly related to consumption in calories or volume, but instead, is a function of orosensory detection with minimal influence from post-ingestive effects (Glendinning et al , 2002, Loney et al , 2012, McCaughey and Glendinning, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief-access lickometry, taste stimuli are presented for a short (seconds) duration. The output lick rate is not directly related to consumption in calories or volume, but instead, is a function of orosensory detection with minimal influence from post-ingestive effects (Glendinning et al , 2002, Loney et al , 2012, McCaughey and Glendinning, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…We used a brief-access lickometer assay, as it is commonly used to identify taste quality and to separate orosensory-mediated responses from higher order responses (Loney et al , 2012, Mantella and Youngentob, 2014, McCaughey and Glendinning, 2013). This assay has been used to quantify differences of taste sensitivity in mice with mutations in taste-related genes (Tordoff and Ellis, 2013, Treesukosol et al , 2009) and to compare orosensory ability and drug preference for both nicotine (Glatt et al , 2009) and alcohol (Brasser et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another measure of ingestive responsiveness is the number of trials that mice initiated across the 30-min test session (McCaughey and Glendinning 2013). However, there were no significant differences in number of trials initiated by sham-and leptin-injected mice when tested with the broad (sham: 41.2 ± 2.9; leptin: 34.7 ± 3.6; unpaired t value = 1.42, df = 12, P = 0.18) or narrow (sham: 38.4 ± 3.2, leptin: 36.3 ± 2.4; unpaired t value = 0.52, df = 26, P = 0.61) range of sucrose concentrations.…”
Section: Does Leptin Alter Concentration-dependent Increases In Lickimentioning
confidence: 99%
“…Consistent with this, rats fed a high-fat and high-sugar diet (45% fat and 17% sugar) for 8 weeks presented dulled nucleus tractus solitarius (NTS; Boxes 1 and 2 ) responses to taste that included lower magnitude and duration and longer latency to sweet solutions and naturalistic taste stimuli [ 44 ]. However, these changes seem to require an extended exposure to dietary sugar because previous work reported an increase in CT responses to sucrose and no changes in the NTS responses following a short, 3-day access to a high-energy diet (45% fat and 17% sugar) [ 45 ] or to a 0.5 M sucrose solution [ 46 ], respectively. These findings are especially interesting when compared with those of two studies in which mice fed a high-fat diet (60% fat and 22% carbohydrates) for 8 weeks showed a decrease in the number of taste buds responsive to sweet stimuli (saccharin and Acesulfame K) and in the amplitude of their calcium responses measured ex vivo with calcium-sensitive dyes [ 47 , 100 ].…”
Section: Diet and Chemosensory Plasticitymentioning
confidence: 99%